2015
DOI: 10.1159/000438719
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Role of the Detection of Human Telomerase RNA Component Gene Amplification by Fluorescence in situ Hybridization on Liquid-Based Cervical Samples: Comparison with Human Papillomavirus-DNA Testing and Histopathology

Abstract: Objective: This study was designed to evaluate whether the adjunct of human telomerase RNA component (hTERC) fluorescence in situ hybridization (FISH) analysis to cytological diagnosis and human papillomavirus (HPV)-DNA testing may serve as a predictive marker for distinguishing cervical lesions destined to regress from those at high risk of progression towards invasive cancer. Study Design: hTERC FISH analysis was performed on 54 residual liquid-based cytology specimens obtained from women referred to colposc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
3
13
0
1
Order By: Relevance
“…The present study reported that h-TERC gene analysis had the highest specificity (81.76%) and the lowest misdiagnosis rate (18.24%). Additionally, the combination of TCT, HPV and h-TERC displayed 100% sensitivity and 98.11% specificity, suggesting h-TERC may be the principal gene in cervical carcinogenesis, which is in line with results from previous studies (19,27). It has been reported that the h-TERC gene is significantly upregulated in numerous cancer types (28,29).…”
Section: Discussionsupporting
confidence: 90%
“…The present study reported that h-TERC gene analysis had the highest specificity (81.76%) and the lowest misdiagnosis rate (18.24%). Additionally, the combination of TCT, HPV and h-TERC displayed 100% sensitivity and 98.11% specificity, suggesting h-TERC may be the principal gene in cervical carcinogenesis, which is in line with results from previous studies (19,27). It has been reported that the h-TERC gene is significantly upregulated in numerous cancer types (28,29).…”
Section: Discussionsupporting
confidence: 90%
“…This approach will reduce over-referral, unnecessary colposcopies, and overtreatment of women without clinically meaningful HPV infections. Currently, various triage strategies for hrHPV-positive women have been considered including repeat cytology testing [15] , HPV16/18 genotyping [16] , [17] (and combinations thereof [15] , [18] ), HPV E7 mRNA analysis [19] , [20] , viral and/or host cell DNA methylation analysis [21] , [22] , [23] , p16/ki67 cytological dual staining [24] , [25] and analysis of host cell gene amplification such as TERC [26] , [27] . Of these, cytology, either or not combined with HPV16/18 genotyping analysis, is currently most widely accepted [15] , [28] .…”
Section: Introductionmentioning
confidence: 99%
“…A high level of hTERT expression with a low level of TGFBR2 (transforming growth factor-β receptor type II) expression correlated with poor prognosis in patients with cervical cancer [ 69 ]. Studies conducted by Zappacosta et al [ 70 ] have indicated the possible application of the hTERC analysis in the diagnostics of CIN2 lesions. Studies on a group of 54 women with ASCUS+ lesions showed that 96.3% had oncogenic HPV-DNA, and the expression of the hTERC gene was confirmed by fluorescence in situ hybridization (FISH) in more than 70% of women with CIN2+ lesions.…”
Section: Potential Application Of Hterc Analysis Amentioning
confidence: 99%